Aedes aegypti anti-salivary proteins IgG levels in a cohort of DENV-like symptoms subjects from a dengue-endemic region in Colombia - Olajiga, Olayinka M.; Marin-Lopez, Alejandro; Cardenas, Jenny C.; Gutierrez-Silva, Lady Y.; Gonzales-Pabon, Maria U.; Maldonado-Ruiz, L. Paulina; Worges, Matt; Fikrig, Erol; Park, Yoonseong; Londono-Renteria, Berlin (Frontiers in Epidemiology, 2022)
Dengue fever, caused by the dengue virus (DENV), is currently a threat to about half of the world's population. DENV is mainly transmitted to the vertebrate host through the bite of a female Aedes mosquito while taking a blood meal. During this process, salivary proteins are introduced into the host skin and blood to facilitate blood acquisition. These salivary proteins modulate both local (skin) and systemic immune responses. Several salivary proteins have been identified as immunogenic inducing the production of antibodies with some of those proteins also displaying immunomodulatory properties enhancing arboviral infections. IgG antibody responses against salivary gland extracts of a diverse number of mosquitoes, as well as antibody responses against the Ae. aegypti peptide, Nterm-34 kDa, have been suggested as biomarkers of human exposure to mosquito bites while antibodies against AgBR1 and NeSt1 proteins have been investigated for their potential protective effect against Zika virus (ZIKV) and West Nile virus infections. Thus, we were interested in evaluating whether IgG antibodies against AgBR1, NeSt1, Nterm-34 kDa peptide, and SGE were associated with DENV infections and clinical characteristics. For this, we tested samples from volunteers living in a dengue fever endemic area in Colombia in 2019 for the presence of IgG antibodies against those salivary proteins and peptides using an ELISA test. Results from this pilot study suggest an involvement of antibody responses against salivary proteins in dengue disease progression.